Electrochemically Driven Strategies Enabling the Construction of Carbon–Carbon/Carbon–Heteroatom Bonds - Dapkekar, Anil Balajirao; Satyanarayana, Gedu (Synlett, 2025)
The scientific community has recently shown a significant interest in electro-organic synthesis, which has been recognized as a promising, environmentally friendly, and sustainable tool for organic synthesis. Here, the electric current acts as a reagent to drive chemical transformations, which avoids the usage of hazardous, oxidizing, and reducing reagents. Therefore, herein, we present an account of recent developments in electrochemical synthetic methodologies that were developed in our laboratory, such as the synthesis of tertiary alcohols, 3-selenylindoles, sulfenyl-phenanthrenes, spiro-cyclohexadienone indenes, β-hydroxy-selenides, 4-sulfenyl-isochromenones, and para-hydroxysulfonamides/acetanilides. We hope this account will provide the feasibility for and further advancements in reaction design, mechanistic understanding, and the pertinence of electro-catalysis in academic and industry frameworks.
Keywords: Electro-catalysis; Electricity as a green redox reagent; Tertiary alcohol; Chalcogen; Paracetamol